Pemeriksaan Terhadap Notaris oleh Majelis Pengawas Notaris Daerah Kabupaten Banyumas Periode Tahun 2022–2025 - Hestin Tri Yulianti; Wahyu Hariadi; Haris Kusumawardana (Faculty of Law, Universitas Wijayakusuma, 2023)
The role and authority of a Notary are very important in people's lives in order to obtain legal certainty for the legal actions taken. In carrying out this role and authority, the behavior and actions of a Notary are very vulnerable to abuse of their professional position, which can be detrimental to society. To avoid losses for the community, an agency that supervises notaries is needed. This research was conducted to find out how the inspection of a notary was carried out by the Regional Supervisory Board of Banyumas Regency for the period 2022-2025 and the obstacles encountered in the examination. The research method uses normative juridical data analysis methods in the form of qualitative analysis. Based on the results of the research, it can be concluded that the supervision, examination, and guidance of Notaries are carried out by the Minister of Law and Human Rights, in whose implementation the Minister forms a Notary Supervisory Council, based on Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary. In this case, the Regional Supervisory Council is the spearhead of the Notary Supervisory Council in carrying out supervision, inspection, and guidance of Notaries. Keywords: Notary, Supervisor, Examination Peranan dan kewenangan Notaris sangat penting dalam kehidupan masyarakat untuk mendapatkan kepastian hukum terhadap perbuatan-perbuatan hukum yang dilakukan. Dalam menjalankan peran dan kewenangan itu, perilaku dan perbuatan yang dilakukan Notaris sangat rentan terhadap penyalahgunaan jabatan profesinya, sehingga dapat merugikan masyarakat. Untuk menghindari kerugian oleh masyarakat itu diperlukan suatu badan yang melakukan pengawasan terhadap Notaris. Penelitian ini dilakukan untuk mengetahui bagaimana pelaksanaan pemeriksaan terhadap Notaris oleh Majelis Pengawas Daerah Kabupaten Banyumas Periode tahun 2022-2025 dan kendala yang dihadapi dalam pemeriksaan tersebut. Metode penelitian menggunakan yuridis normatif dengan metode analisis data berupa analisis kualitatif. Berdasarkan hasil penelitian, dapat disimpulkan bahwa pengawasan, pemeriksaan dan pembinaan terhadap Notaris dilakukan oleh Menteri Hukum dan HAM yang dalam pelaksanaanya Menteri membentuk Majelis Pengawas Notaris (MPN), berdasarkan UU No 2 tahun 2014 tentang Perubahan atas UU No 30 tahun 2004 tentang Jabatan Notaris. Dalam hal ini, MPD merupakan ujung tombak dari MPN dalam melakukan pengawasan, pemeriksaan dan pembinaan terhadap Notaris. Kata Kunci: Notaris, Pengawas, Pemeriksaan